Transplant of SARS-CoV-2–infected Living Donor Liver: Case Report. Issue 8 (8th July 2021) - Nguyen, Michelle C.; Lee, Eliza J.; Avery, Robin K.; Dioverti-Prono, M. Veronica; Shoham, Shmuel; Tobian, Aaron A. R.; Bloch, Evan M.; Gurakar, Ahmet; Rizkalla, Nicole A.; Cameron, Andrew M.; King, Elizabeth A.; Ottmann, Shane; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Given the high community prevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), transplant programs will encounter SARS-CoV-2 infections in living donors or recipients in the perioperative period. There is limited data on SARS-CoV-2 viremia and organotropism beyond the respiratory tract to inform the risk of transplant transmission of SARS-CoV-2. We report a case of a living donor liver transplant recipient who received a right lobe graft from a living donor with symptomatic PCR-confirmed SARS-CoV-2 infection 3 d following donation. The donor was successfully treated with remdesivir, dexamethasone, and coronavirus disease 2019 (COVID-19) convalescent plasma. No viral transmission was identified, and both donor and recipient had excellent postoperative outcomes.